Volatile Constituents of Matricaria chamomilla L. from Isfahan, Iran: Volatile oil of Matricaria chamomilla L - Shams-Ardakani, Mohammadreza; Ghannadi, Alireza; Rahimzadeh, Azadeh (Iranian Journal of Pharmaceutical Sciences, 2006)
The volatile oil obtained by hydrodistillation of the aerial parts of Matricaria chamomilla L. (Asteraceae) growing in Botanical Garden, Isfahan University of Medical Sciences, Iran, was investigated by gas chromatography (GC) and GC/ mass spectrometery (MS). Sixty-three components were characterized, representing 86.21% of the total oil components detected. α-Bisabolol oxide A(25.01%) and abisabolol oxide B (9.43%) were the major constituents of the oil.